Geodynamics Based on Solidification of Liquid/Molten Substances in the Earth’s Interior - Li, Xin; Tao, Mingjiang; He, Duanwei (Frontiers in Earth Science, 2022)
Since its formation, the Earth has cooled from molten magma to the present layered structure. The liquid and molten substance in the interior of the Earth continuously solidifies, radiating heat to the outer space and causing changes in the pressure and density inside the Earth. Constrained by the rigid lithosphere, the change in density decreases the pressure at the bottom of the crust, and thereby supports the rigid lithosphere. Under the effect of gravity, there is an increased interaction between tectonic plates, which leads to local stress accumulation. Eventually, this stress exceeds the strength of the rock and makes the mechanical structure of the crustal lithosphere unstable. This process is iterative, and the Earth continuously adjusts to new mechanical equilibria by releasing the accumulated stress through geological events such as earthquakes. In this study, using three sets of observations (Global Positioning System data, length of day data, and the latent heat of Earth solidification), we show that these observations are consistent with the aforementioned assumption that the solidification of liquid cause changes in density and volume in the Earth’s interior. Mechanical analyses indicate that liquid solidification in the interior of the Earth leads to decrease in the Earth’s volume. This increases the intensity of plate interactions, which leads to the movement of large plates, triggering geological events such as earthquakes. Thus, it is determined that liquid solidification in the Earth’s interior is the main source for the movement of plates.